The Differences of Enamel Rod Patterns on the Tooth before and after Burning as a Tooth Prints - Prameswari, Kirana Herwinda; Prawestinigtyas, Eriko; Swastirani, Astika (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The tooth can stand by postmortem effects such as fire because of high temperature, and tooth enamel will have to increase in crystallization of hydroxyapatite so that it can still withstand. Enamel consists of enamel rods that microscopically have a unique pattern called tooth prints. The study aims to determine the differences between enamel rod patterns before and after being burnt as a determinant of tooth prints. The study used 30 maxillary first premolar that was randomly selected. The recording of enamel rod patterns was done using the cellulose acetate peeling technique. It did the recording before burnt (antemortem) and after being boiled at 650oC for 15 minutes (postmortem). Tooth prints which are the results of recording enamel rod pattern, were analyzed using Verifinger SDK v.4.2 to obtain a minute score, and then a statistical test was performed. The development of the statistical test showed no significant difference in enamel rod pattern between before and after being burnt (paired T-test, p=0,175). This study concludes that there is no significant difference in enamel rod patterns between before and after being burnt, showing that tooth prints can be used as an alternative for forensic identification in fire victims.